Um olhar estético sobre o telespetáculo esportivo :contribuições para o ensino do esporte na escola - Araújo, Allyson Carvalho de (2006)
The sportive television spectacle shows up like a media phenomenon which evidence performances and techniques that further on the community realized in the quotidian sportive practices into a show and play mixer, that more and more, sensibility the viewers. In this scenery , this research is about the relation between sportive television spectacle and viewer by the aesthetics perspective, and discussed the sport in the Physical Education context with the focus in the contributions to teaching in the school. The research, to the methodological view, uses the discuss analysis and realizes a qualitative study in two interdependent moments. In the first, analysis the dada collated in the Education, sport and television workshop. In the second, turns about TV images of sportive television spectacle to appreciated, to support a discuss of these phenomenon s aesthetics elements, looking for the relation established between the sportive television spectacle and viewer. The analysis s emphasis is in the sensations by sportive television spectacle, as well in the aesthetic elements problems promoted by this experience, from the two basics concepts, to know: the aesthetic and the synaesthetic perception. The analysis s corpus is composed by Esporte Espetacular TV program. Identify, in the sportive television spectacle appreciation, four big discuss axis of great importance between sportive television spectacle and viewer understanding: the relation space and time, the belonging feeling, the language interlacing, and beauty models. Understand in the analysis that, in the sportive TV scenery, occurs a construction image that seduces and involves the viewer through the aesthetics elements. From that discuss axis reflect about teaching sport in the school, main concern to the materialization a sport model only. Aims unfolding about space and time construction yet, and about the multiplicity language for to work in the school. Positions that no absolute rules, but that check the TV sport by the seduction promoted in the viewers through the aesthetics elements transmit